Data-driven classification and design of bioactive cellulose acetate electrospun films for active food packaging - Ahmad Rabbani; Anuj Niroula; Muhammad Z. Iqbal; Sajid Maqsood; Akmal Nazir (PLoS ONE, 2026)
The development of bio-based food packaging materials is increasingly important for reducing reliance on petroleum-based plastics. For practical packaging use, these materials must also achieve suitable mechanical performance, including strength, flexibility, and stiffness. This study reports the fabrication of bioactive cellulose acetate (CA) films containing aloe vera gel (AG) and lemongrass essential oil (EO) using electrospinning, aimed at developing mechanically robust films with potential relevance to active food packaging applications. Mechanical performance was systematically assessed across 11 formulations generated by a Latin Hypercube Design. Tensile strength (TS), elongation at break (EAB), and Young’s modulus (YM) were measured, and response surface methodology was employed to model the effects of CA, AG, and EO, including their interactions. CA emerged as the primary determinant, improving TS and YM but reducing EAB at higher concentrations. AG functioned as a natural plasticizer, enhancing flexibility while lowering stiffness, whereas EO showed conditional effects, providing limited plasticization at low concentrations and reduced mechanical integrity when combined with elevated CA or AG concentrations. Trade-offs between the measured properties emphasized the role of interactions rather than single components. Films were subsequently classified into flexible, balanced, and rigid categories based on the experimental thresholds, linking formulations with potential packaging applications and providing a basis for rational design of biodegradable packaging materials.